Synthesis of enones, pyrazolines and pyrrolines with gem-difluoroalkyl side chains - El Dine, Assaad Nasr; Khalaf, Ali; Grée, Danielle; Tasseau, Olivier; Fares, Fares; Jaber, Nada; Lesot, Philippe; Hachem, Ali; Grée, René (Beilstein Journal of Organic Chemistry, 2013)
Starting from easily accessible gem-difluoropropargylic derivatives, a DBU-mediated isomerisation affords enones in fair yields with a gem-difluoroalkyl chain. These derivatives were used to prepare pyrazolines and pyrrolines with the desired gem-difluoroalkyl side chain by cyclocondensations in good yields and with excellent stereoselectivity. A one-pot process was also successfully developed for these sequential reactions. By carrying out various types of Pd-catalyzed coupling reactions for compounds with a p-bromophenyl substituent a route to focused chemical libraries was demonstrated.
Keywords: 19F/1H HOESY; gem-difluoroalkyl derivatives; organo-fluorine compounds; palladium catalysis; pyrazolines; pyrrolines

Biomedical Frontiers in Fluorine Chemistry - Ojima, I.; McCarthy, J. R.; Welch, J. T. (American Chemical Society, 1996)

Fluorine in Bioorganic Chemistry - Welch, J. T.; Eswarakrishnan, S. (Wiley-Interscience, 1991)

(untitled) - Welch, J. T. (Tetrahedron, 1987)

(untitled) - Isanbor, C.; O'Hagan, D. (J. Fluorine Chem., 2006)

(untitled) - Bégué, J.-P.; Bonnet-Delpon, D. (J. Fluorine Chem., 2006)

(untitled) - Kirk, K. L. (J. Fluorine Chem., 2006)

(untitled) - Hagman, W. K. (J. Med. Chem., 2008)

(untitled) - Filler, R.; Saha, R. (Future Med. Chem., 2009)

(untitled) - O’Hagan, D. (J. Fluorine Chem., 2010)

(untitled) - Dolle, R. E.; Le Bourdonnec, B.; Worm, K.; Morales, G. A.; Thomas, C. J.; Zhang, W. (J. Comb. Chem., 2010)
And references cited therein.

(untitled) - Welsh, M. E.; Snyder, S. A.; Stockwell, B. R. (Curr. Opin. Chem. Biol., 2010)
And references cited therein.

(untitled) - Prakesch, M.; Grée, D.; Grée, R. (Acc. Chem. Res., 2002)

(untitled) - Pacheco, M. C.; Purser, S.; Gouverneur, V. (Chem. Rev., 2008)
And references cited therein. See for a comprehensive review on the chemistry of propargylic allylic fluorides.

(untitled) - Prakesch, M.; Kerouredan, E.; Grée, D.; Grée, R.; DeChancie, J.; Houk, K. N. (J. Fluorine Chem., 2004)

(untitled) - Manthati, V. L.; Grée, D.; Grée, R. (Eur. J. Org. Chem., 2005)

(untitled) - Manthati, V. L.; Murthy, A. S. K.; Caijo, F.; Drouin, D.; Lesot, P.; Grée, D.; Grée, R. (Tetrahedron: Asymmetry, 2006)
And references cited therein.

(untitled) - Grée, D.; Grée, R. (Tetrahedron Lett., 2007)

(untitled) - Pujari, S. A.; Kaliappan, K. P.; Valleix, A.; Grée, D.; Grée, R. (Synlett, 2008)

(untitled) - Blayo, A.-L.; Le Meur, S.; Grée, D.; Grée, R. (Adv. Synth. Catal., 2008)

(untitled) - Bannwarth, P.; Valleix, A.; Grée, D.; Grée, R. (J. Org. Chem., 2009)

(untitled) - Bannwarth, P.; Grée, D.; Grée, R. (Tetrahedron Lett., 2010)

(untitled) - Bannwarth, P.; Grée, D.; Das, S.; Yadav, J. S.; Grée, R. (J. Fluorine Chem., 2012)

(untitled) - Arimitsu, S.; Fernández, B.; del Pozo, C.; Fustero, S.; Hammond, G. B. (J. Org. Chem., 2008)
See for preparation of other series of fluoropropargylic derivatives by a completely different route.

(untitled) - Xu, B.; Hammond, G. B. (Angew. Chem., Int. Ed., 2005)
See for preparation of other series of fluoropropargylic derivatives by a completely different route.

(untitled) - Wang, Z. G.; Hammond, G. B. (J. Org. Chem., 2000)
See also references cited therein and for preparation of other series of fluoropropargylic derivatives by a completely different route.

(untitled) - Nineham, A. W.; Raphael, R. A. (J. Chem. Soc., 1949)

(untitled) - Sonye, J. P.; Koide, K. (J. Org. Chem., 2007)

(untitled) - Yamazaki, T.; Kawasaki-Takasuka, T.; Furuta, A.; Sakamoto, S. (Tetrahedron, 2009)

(untitled) - Marella, A.; Ali, Md. R.; Alam, Md. T.; Saha, R.; Tanwar, O.; Akhter, M.; Shaquiquzzaman, Md.; Alam, M. M. (Mini-Rev. Med. Chem., 2013)

(untitled) - Müller, T. J. J.; Ansorge, M.; Aktah, D. (Angew. Chem., Int. Ed., 2000)

(untitled) - Bellina, F.; Rossi, R. (Tetrahedron, 2006)

(untitled) - Zhang, Y.; Ran, C.; Zhou, G.; Sayre, L. M. (Bioorg. Med. Chem., 2007)

(untitled) - Kawai, H.; Yuan, Z.; Kitayama, T.; Tokunaga, E.; Shibata, N. (Angew. Chem., Int. Ed., 2013)

(untitled) - Marrec, O.; Christophe, C.; Billard, T.; Langlois, B.; Vors, J.-P.; Pazenoc, S. (Adv. Synth. Catal., 2010)

(untitled) - Miyaura, N.; Suzuki, A. (Chem. Rev., 1995)

(untitled) - Heck, R. F.; Nolley, J. P., Jr (J. Org. Chem., 1972)

(untitled) - Sonogashira, K. (J. Organomet. Chem., 2002)